Investigating the Reading Difficulties of Magister Students of Physics vis-à-vis Their General English knowledge, University of Constantine - AZEROUAL, Djihed (Journal of Human Sciences, 2014)
This paper reports on a study which investigates the reading comprehension problems and difficulties of magister students of Physics while reading scientific texts and elicits their reading difficulties in English. The results were obtained from a students’ questionnaire and a test. The analysis of the data proved that the students’ difficulties are due to their linguistic handicap mainly in grammar and vocabulary. Furthermore, it confirms that these students’ have a poor level in General English which compounds their reading comprehension difficulties. These results lead us to believe that the teaching/ learning situation of English at the Physics Department, at the University of Constantine should be re-considered. For that, we suggest to implement reading courses to reinforce the students’ General English knowledge and promote their reading comprehension of scientific texts